Peran Ganda Petani Perempuan dalam Memenuhi Kebutuhan Rumah Tangga di Desa Sukarame Kecamatan Cikeusal - Suntiyah, Suntiyah; Hayat, Nurul (Lembaga Yasin AlSys, 2022)
This study aims to determine how the dual role of women farmers in Sukarame Village. The method used in this research is descriptive qualitative to try to see or describe the dual role of farmers in meeting household needs, the data collection technique is observational documentation by going directly to the field with interviews, research results, scientific journals related to the research that I do. From the results of this study it was found that women in Sukarame Village have a dual role in the domestic sector and the public sector, where in the domestic sector the role of women farmers as housewives such as cooking, washing, taking care of children etc. And in the public sector the role of women is to carry out a dual role as farmers to meet the economic needs of the family by working as farmers to achieve prosperity, so that the livelihoods of the people of Sukarame Village on average are farmers and are dominated by women. double in their work activities but do not forget their role as housewives because the women of Sukarame Village consider that housework is a job that must be done as a wife.